ANALISIS MUTU DAN KUALITAS INPUT-PROSES-OUTPUT PENDIDIKAN DI MAN 2 YOGYAKARTA - Uswatun Hasanah (MANAGERE : Indonesian Journal of Educational Management, 2020)
This study aims to examine the analysis of the quality and quality of education in islmaic educational institutions in MAN 2 Yogyakarta. The research method used is descriptive analysis with a qualitative approach. Data collection techniques are done by interview, observation and documentasion. The results showed that; 1). To achieve the vision, mission and objectives of the Madrasah, the principal plays an active role in assisting and communicating to teachers and staff in realizing the vision and mission of the Madrasah by realizing knowledgeable, charitable and noble personality; 2). MAN 2 Yogyakarta has excellent academic and non-academic achievements; 3). Graduates or graduates of MAN 2 Yogyakarta are able to compete with other Madrasah to continue in Indonesia’s best universities, such as UGM, UNY, IPB, UIN Sunan Kalijaga, and Jendral Sudirman University; 4). To be a superior Madrasah, MAN 2 Yogyakarta is still not superior enought, that is because there are some facilities and infrastructure that have not been fulfilled properly.